Mechanical properties of adobe bricks using sawdust as partial sand replacement - Syarifah Nur Farhana, Said Mostafa (2017)
Adobe were traditionally produced by mixing soil, sand and water to plastic consistency. It is building material used to make walls, pavements and other components in masonry construction. Customarily, the term brick referred to a unit composed of clay, yet it is presently used to denote any rectangular units laid in mortar. Over the past several decades, the demand for bricks has been increasing rapidly for the housing. Industrial wastes will gives the hazardous impact to environment and people because, although these waste are burnt, they release the carbon monoxide to atmosphere which can depletes the ozone layer. So, there is need to investigate the use of alternative building materials which are locally available such as sawdust, the most abundant waste that have been dumped in landfill area. Today, many alternatives are use in order to improve the properties of adobe brick. One of the best options is by adding the waste material into it to replace sand which in high demand. The sawdust that generate from the wood at sawmill usually end up at will be feed to the livestock or being dumped at landfill. Surprisingly, the characteristics of both materials which are sand and sawdust are almost identical. By replacing sand with sawdust, sand mining and waste disposal problems can be reduced as well as economical adobe brick can be produced. This study aims to investigate the effect of sawdust as partial sand replacement on the properties of adobe brick. The field of studies also covers important parameters including compressive strength and flexural strength in determining the engineering properties. The compressive and flexural tests for these required parameters will be conducted on 3 weeks after the adobe bricks undergo air curing.